D: k= 36 it is that one because it’s a big number
Split the second term 7x^2 - 8x - 12 into two terms
7x^2 + 6x - 14x - 12
Factor out common terms in the first two terms, then in the last two terms
x(7x + 6) - 2(7x + 6)
Factor out the common term; 7x + 6
<u>(7x + 6)(x - 2) </u>
Answer:
369
Step-by-step explanation:
g(f(x)) simply means to put the whole expression of function f(x) into the place of "x" in g(x).
and to find the functional value for a specific x we just need to calculate functional value for f(x) and use that result as input for g(x).
f(6) = 8×6 + 5 = 48 + 5 = 53
and now
g(53) = 7×53 - 2 = 371 - 2 = 369
to check we do the general functional substitution :
g(f(x)) = 7×(8x+5) - 2 = 56x + 35 - 2 = 56x + 33
g(f(6)) = 56×6 + 33 = 336 + 33 = 369
correct
Answer:
Which of the following plans include a savings plan as a part of the insurance?
Whole Life
Universal Life
<u>Variable Universal Life</u>
All of the above
Step-by-step explanation:
the cost of the eggs
cost (x) = x*price
this is an example of a proportional cost relation with the size been x